Hydroclimate variability in the Madagascar and Southeast African summer monsoons at the Mid- to Late-Holocene transition. (15th January 2023) - Scroxton, Nick; Burns, Stephen J.; McGee, David; Godfrey, Laurie R.; Ranivoharimanana, Lovasoa; Faina, Peterson; Tiger, Benjamin H.
Abstract: The 4.2 ka event at the Mid- to Late-Holocene transition is often regarded as one of the largest and best documented abrupt climate disturbances of the Holocene. The event is most clearly manifested in the Mediterranean and Middle East as a regional dry anomaly beginning abruptly at 4.26 kyr BP and extending until 3.97 kyr BP. Yet the impacts of this regional drought are often extended to other regions and sometimes globally. In particular, the nature and spatial extent of the 4.2 ka event in the tropics have not been established. Here, we present a new stalagmite stable isotope record from Anjohikely, northwest Madagascar. Growing between 5.22 and 2.00 kyr BP, stalagmite AK1 shows a hiatus between 4.31 and 3.93 kyr BP (±40 and ± 35 yrs), replicating a hiatus in another stalagmite from nearby Anjohibe, and therefore indicating a significant drying at the Mid- to Late-Holocene transition. This result is the opposite to wet conditions at the 8.2 ka event, suggesting fundamentally different forcing mechanisms. Dry conditions are also recorded in sediment cores in Lake Malawi, Lake Masoko and the Tatos Basin on Mauritius, also in the southeast African monsoon domain. However, no notable event is recorded at the northern (equatorial East Africa) and eastern (Rodrigues) peripheries of the monsoon domain, while a wet event is recorded in sediment cores at Lake Muzi and Mkhuze Delta to the south. The spatial pattern is largely consistent with the modern rainfall anomaly pattern associated a with weak Mozambique Channel Trough and a northerly austral summer Intertropical Convergence Zone position. Within age error, the observed peak climate anomalies overlap with the 4.2 ka event. However regional hydrological change consistently begins earlier than a 4.26 kyr BP event onset. Gradual hydrological change frequently begins around 4.5 kyr BP, raising doubt as to whether any coherent regional hydrological change is merely coincident with the 4.2 ka event or part of a global climatic anomaly. Graphical abstract: Image 1 Highlights: We present a new stalagmite record of Holocene monsoon variability from northwest Madagascar. A growth hiatus coincident with the 4.2 ka event is replicated in multiple stalagmites. A dry climate anomaly is opposite to the wet anomaly seen at the 8.2 ka event. The regional pattern of rainfall anomalies around 4.2 kyr BP resembles a weak Mozambique Channel Trough. Regional anomalies consistently begin around 4.5 kyr BP, raising doubt as to a 4.2 ka event forcing.